Prevalence of the MTHFR C677T Mutation in Fertile and Infertile Women - Soligo, Adriana de Góes; Barini, Ricardo; Annichino-Bizzacchi, Joyce Maria (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2017)
Introduction The importance of the C677T mutation in the methylenetetrahydrofolate reductase (MTHFR) gene in infertile women remains controversial.Objective To evaluate if the MTHFR C677T mutations are more frequent in infertile women, and if they can be associated with the occurrence of infertility in the Brazilian population.Methods This case-control study included 130 infertile women consulting at a private clinic between March 2003 and March 2005 (data previously published), and 260 fertile women attending the family planning outpatient clinic of our institution between April 2012 and March 2013. Data analysis The Chi-squared and Fisher Exact tests were used to evaluate the association between the presence of the MTHFR C677T mutation and a history of infertility.Results The frequency of the mutation was of 58.5% for the case group (n = 76) and of 49.2% for the fertile controls (n = 128). The mutation was homozygous in 13 women in the case group (10%) and in 23 of the fertile women in the control group (8.8%). These differences were not statistically significant.Conclusions These results suggest that the presence of the MTHFR C677T mutation does not constitute a risk factor for infertility, even when the mutation is homozygous. Further studies are needed to confirm whether research on this mutation should be considered unnecessary in women with infertility.
Keywords: infertility; thrombophilia; MTHFR C677T mutation